14 Phase II trial evaluating efficacy and safety of standard of care with or without bevacizumab in platinum-resistant epithelial ovarian, fallopian tube, or primary peritoneal cancer. (13th November 2020) - Nishikawa, N; Shoji, T; Enomoto, T; Abe, M; Okamoto, A; Saito, T; Oishi, T; Nagase, S; Mori, M; Inokuchi, Y; Kamiura, SK; Sugiyama, T
Abstract : Introduction: There are no ongoing clinical trials investigating bevacizumab efficacy beyond disease progression in platinum-resistant recurrent ovarian cancer; however, improving outcomes in these patients is a critical unmet need. Methods: This open-label, randomized phase II trial (JGOG3023; UMIN000017247) enrolled patients aged ≥20 years with histologically confirmed epithelial ovarian, fallopian tube, or primary peritoneal carcinoma with platinum-resistant disease (progression occurring ≤6 months from completing ≥3 platinum cycles, including bevacizumab). Patients were randomized 1:1 to single-agent chemotherapy (group A) or single-agent chemotherapy combined with bevacizumab (group B). The primary endpoint was investigator-assessed PFS. Secondary endpoints included OS, ORR, and safety. Results: Patient characteristics were balanced between group A (n=51) and group B (n=52). Median PFS was longer in group B versus group A (4.0 [95% CI: 3.0–5.7] vs 3.1 [2.5–4.6] months; HR, 0.54 [0.32–0.90]; one-sided p=0.0082) (figure 1 ). Maximum tumor diameter and ascites were significantly associated with greater prolongation in PFS in group B (figure 2 ). Median OS was numerically longer in group B versus group A (15.3 vs 11.3 months; HR, 0.67 [0.38–1.17]; two-sided p=0.1556). ORR was 13.7% and 25.0% in group A and B, respectively. The safety profile was similar across both groups (table 1 ). Conclusion: These results suggest chemotherapy combined with bevacizumab has efficacy beyond disease progression. A phase III trial is warranted to confirm our findings.